Case report: Resolution of oligo-anuric acute kidney injury with furosemide administration in a cat following lily toxicity - To, An; Davila, Claudia; Stroope, Sarah; Walton, Rebecca (Frontiers in Veterinary Science, 2023)
Objective: To describe the successful outcome of a case of oligo-anuric acute kidney injury in a cat secondary to lily ingestion. Case Summary: A 12-week-old intact male domestic short hair cat weighing 1.64 kg (3.6 lb) presented with a 12-hour duration of vomiting and lethargy after exposure to lilies of the genera Lilium species 24 hours prior to presentation. Severe azotemia (Creatinine 5.8 mg/dL, BUN > 100 mg/dL) and hyperkalemia (9.36 mmol/L) were noted on the day of presentation. Treatment of hyperkalemia was instituted with calcium gluconatea, lactated ringers solutionb, dextrosec, regular, short acting insulin d, albuterolf, and sodium bicarbonateg. Oliguria to anuria was highly suspected based on lack of urine production 21 hours after hospitalization with intravenous fluid administration and a static bladder size. The cat was administered 4mg/kg of furosemidek and urinated 6 hours following administration and continued to produce over 6 ml/kg/hr of urine in the next 24 hours. Two days following furosemide administration the cat’s hyperkalemia and azotemia resolved. The cat was discharged after 4 days of hospitalization and recheck revealed no persistent azotemia or hyperkalemia. Unique Information: Anuric acute kidney injury secondary to lily toxicity is associated with a poor prognosis and the only treatment modality previously described is hemodialysis. The cat in this report was successfully managed with medical intervention and furosemide administration, with complete resolution of the acute kidney injury.